Liquidation value and loan pricing - Francesca Barbiero; Glenn Schepens; Jean-David Sigaux (European Central Bank (ECB), 2022)
We show that the liquidation value of collateral depends on who is pledging it. We employ transaction-level data on overnight repurchase agreements (repo) and loan-level credit registry data on corporate loans. We find that borrowers on the repo market pay a 2.6 basis points rate premium when their default risk is positively correlated with the risk of the collateral that they pledge. The premium in corporate loan markets amounts to 25 basis points. Our results imply that liquidation value contains a component at the borrower-collateral level, and that lenders monitor and price-in the interdependency between borrower and collateral risk.
Keywords: G21; G12; D53; D47; E43; 330; Collateral; Money markets; Corporate loans; Wrong-way risk; LGD